The Outcome Of Labour With Epidural Analgesia - A Retrospective Study - Ahmad, Mas Adi (2001)
The objectives of this study are to determine the association between epidural analgesia and the mode of delivery by SVD and non SVD ; to determine the effect of epidural analgesia on the duration of the first and second stages of labour; and to evaluate the influence of gravidity, oxytocin augmentation, previous scar and foetal birth weight on the above effects and associations. A retrospective study was carried out in the Department of Obstetrics and Gynaecology, Universiti Sains Malaysia, utilizing data of deliveries over a 16 month period from February 1999 until May 2000. This comprises randomly selected patients delivering without epidural analgesia within the first 8 months and all patients delivering with epidural analgesia in the other 8 months of the study period. Inclusion criteria are singleton pregnancy with cephalic presentation while exclusion criteria are multiple pregnancy, precipitate labour and patients with indications for elective caesarean section. Labour and delivery data were obtained from patients' case notes and analyzed for associations and significance with Chi Square Test or T-Test. Statistical significance was taken asP value of less than 0.05. Seventy five patients with epidural analgesia and 96 patients without epidural analgesia have been analyzed in this study. Epidural analgesia was associated with a significant ( p = 0.001 ) increase in non SVD. The Odds Ratio for a patient with epidural analgesia delivering by non SVD was 4.05 as compared to a patient without epidural analgesia. Patients' gravidity, oxytocin augmentation, presence of previous scar and foetal birth weight did not alter this association but significance was only demonstrated in non previous scar and patients with fetal weight of 3200 gm or less. Epidural analgesia was associated with longer mean duration of the first stage of labour compared to non epidural patients ( p = 0.003 ). This association was only altered by oxytocin augmentation and presence of previous scar. Significance in the associations were only demonstrated in patients with fetal weight of 3200 gm or less and patients without previous scar. Epidural analgesia was associated with a longer mean duration of the second stage ( p = 0.001 ). This association was not altered by the patients' gravidity, oxytocin augmentation, presence of previous scar or the fetal birth weight. However, significance was only demonstrated in multigravida, oxytocin-augmented patients, non previous scar patients and both larger and smaller foetus (3200 gm or less and more than 3200 gm ). Epidural analgesia significantly increased the risk of non SVD and increased the mean duration of the first and second stages of labour. Only oxytocin augmentation and presence of previous scar altered the association between epidural analgesia and a longer mean duration of first stage of labour, while the other factors did not. None of the evaluated factors, that is patients' gravidity, oxytocin augmentation, previous scar and foetal birth weight altered the positive risk association between epidural analgesia and non SVD; or the association between epidural analgesia and a longer mean duration of the second stage.